Back-channeling in Celebrities Interviews: A Socio-discoursal Study - Zainab Saad Mohammed; Ahmed Adel Nouri (Zanco Journal of Humanity Sciences)
Conversation is an act in which two or more interlocutors take turns. Each one of them speak at a time; hence the act is not something arbitrarily done. However, there might happen some problems when certain interlocutor competes for taking the turn. Conversely, the interlocutor may contribute in some way to the conversation's success and continuance. They assist and facilitate the speaker's speech by employing backchannels.